2007
DOI: 10.1162/rest.89.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Births, Deaths, and New Deal Relief during the Great Depression

Abstract: The article examines the impact of New Deal relief programs on infant mortality, non-infant mortality, and general fertility rates in major U.S. cities between 1929 and 1940. Effects are estimated using a variety of specifications and techniques for a panel of 114 cities that reported information on relief spending between 1929 and 1940. The significant rise in relief spending during the New Deal contributed to reductions in infant mortality, suicide rates, and some other causes of death, while contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(95 citation statements)
references
References 39 publications
5
89
0
1
Order By: Relevance
“…A key message of our previous work was that the consequences of recessions depend largely on how governments respond 5. One of our authors has shown that states with Democratic governors who increased New Deal social protection more than Republican governors, saw greater reductions in child mortality 6. We never excluded outcomes other than suicides and road traffic fatalities, but these appear to be the most plausible in the short term, and are consistent with our7 and others8 data, as well as evidence from the current European recession 9…”
supporting
confidence: 80%
“…A key message of our previous work was that the consequences of recessions depend largely on how governments respond 5. One of our authors has shown that states with Democratic governors who increased New Deal social protection more than Republican governors, saw greater reductions in child mortality 6. We never excluded outcomes other than suicides and road traffic fatalities, but these appear to be the most plausible in the short term, and are consistent with our7 and others8 data, as well as evidence from the current European recession 9…”
supporting
confidence: 80%
“…Data on 50 leading causes of death in the then 115 US cities, which were located in 36 US states, were taken from the US Bureau of the Census for the years 1929–1937,43 building on the existing dataset of Fishback, Haines, and Kantor 29. Washington DC was excluded because of the lack of corresponding state data.…”
Section: Methodsmentioning
confidence: 99%
“…One aggregated analysis by the former editor of the BMJ , Douglas Swinscow, reported a positive correlation between unemployment and suicide in Britain between 1923 and 1947 28. A more recent study of the New Deal and mortalities by economic historians reported short-term associations of spending on social protection during the New Deal with reduced mortality due to infectious and parasitic disease, diarrheal disease, and suicides (using data on fluctuations in retail sales at the city level),29 while that by Tapia Granados and Diez Roux found that, at a national level in the USA, using 21 data points, recessions during the 1920s and 1930s coincided with an overall decline in mortality, consistent with their earlier research elsewhere 17…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been much work in the economics and demographic literature to understand how individuals make fertility decisions and how fertility trends have evolved over time, less work has been done to understand the relationship between U.S. government programs and local fertility. One exception finds that New Deal relief positively influenced fertility (Fishback, Haines, and Kantor 2007). Other work has looked at this relationship in developing countries and found, for instance, that cash transfers in Honduras increased fertility, but there was no distinguishable effect for similar programs in Mexico and Nicaragua (Stecklov et al 2007).…”
Section: Public Programs and Changes In Fertilitymentioning
confidence: 99%
“…Therefore we rely on the General Fertility Rate (GFR), calculated as the number of births divided by the number of women aged 15-44 for our municipal measure of fertility. 5 In historical settings it is often difficult to obtain age-specific fertility rates required for the TFR, so many historical studies use GFR or a related index (Fishback, Haines, and Kantor 2007;Haines and Guest 2008;Jones and Tertilt 2008;David and Sanderson 1987). Although the GFR does not take age structure into account, its year-to-year changes are very similar to the year-to-year changes indicated by the TFR during the study period.…”
Section: Measuring Local Fertilitymentioning
confidence: 99%